Metamorfosis Layanan Produk Lembaga Keuangan Mikro Syariah - Saiful Bakhri; Siti Pamrih Anjas Wulandari (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2020)
Islamic microfinance institutions are one of the pillars in the financial intermediation process. Microfinance is needed by small and medium-sized groups of people for both consumption and production as well as saving their business results. The results of the study indicate that the development of LKMS products is through the company's planning process to find out market desires, make strategic decisions in product formation, improve products, and even make new product innovations as an effort to improve the quality of LKMS services and products. This is a form of improving managerial quality in LKMS. Abstract